To analyze the problem, let's start with the function given:
\[ y = x^2 - 4 \]
Step 1: Find the x-intercepts of the original function
To find the x-intercepts, we set \( y = 0 \):
\[ 0 = x^2 - 4 \]
This simplifies to:
\[ x^2 = 4 \] \[ x = \pm 2 \]
Thus, the original function \( y = x^2 - 4 \) has 2 x-intercepts at \( x = 2 \) and \( x = -2 \).
Step 2: Reflect the function about the origin
When reflecting a function about the origin, we replace \( (x, y) \) with \( (-x, -y) \). Therefore, the reflected function is:
\[ y = -(x^2 - 4) \] \[ y = -x^2 + 4 \]
This is equivalent to:
\[ y = -x^2 + 4 \]
Step 3: Find the x-intercepts of the reflected function
To find the x-intercepts of \( y = -x^2 + 4 \), we set \( y \) to 0:
\[ 0 = -x^2 + 4 \]
This simplifies to:
\[ x^2 = 4 \] \[ x = \pm 2 \]
Thus, the reflected function \( y = -x^2 + 4 \) also has 2 x-intercepts at \( x = 2 \) and \( x = -2 \).
Conclusion
Both the original function and the reflected function have 2 x-intercepts. Therefore, the correct answer to the question regarding the number of x-intercepts of the reflected function is:
Option #3: 2 x-intercepts.